Alkenyl-functional polydiorganosiloxane compositions and methods of use in forming wood-plastic composites
Patent Information
- Application Number
- JP2021200050
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-07
- Filing Date
- 2021-12-09
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2040-06-10
Smart Images

Figure 0007634469000001 
Figure 0007634469000002 
Figure 0007634469000003
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority under 35 U.S.C. §119(e) to U.S. Provisional Application No. 62 / 883,682, filed August 7, 2019. U.S. Provisional Application No. 62 / 883,682 is incorporated herein by reference. [Background technology]
[0002] The polydiorganosiloxanes are useful in wood plastic composite (WPC) compositions and methods for preparing WPC articles. The polydiorganosiloxanes can be provided in liquid or solid form. Summary of the Invention [Problem to be solved by the invention]
[0003] Conventional processes for manufacturing WPC articles generally require processing aids (which may be internal or external) to facilitate the formation of the WPC article and ensure its quality (e.g., surface and edge smoothness). Conventional low-cost organic processing aids generally have the disadvantage of needing to be included in large amounts to increase production rates, which impacts cost and / or performance properties. In addition, many of the conventional processing aids can adversely affect physical properties and reduce the mechanical properties (such as impact resistance, flexural strength, and flexural modulus) of the WPC article, especially at high use temperatures. Conventional processing aids can also migrate out of the WPC article, which can adversely affect one or more properties of the WPC article over time, such as the physical properties, appearance, feel, ability to overmold, ability to coextrude, ability to adhere to, ability to print on, or ability to paint on a surface. In addition, some of the organic processing aids volatilize at high application temperatures, which can lead to the formation of bubbles and cracks in the WPC article, which can impair the long-term performance of these articles. [Means for solving the problem]
[0004] The composition comprises (a) a lignocellulosic filler, (b) an ethylene-based polymer, and (c) a polydiorganosiloxane having at least one silicon-bonded alkenyl group per molecule and having a viscosity of 2,000 mPa·s to 60,000 mPa·s when measured at 25° C. and 0.1 to 50 RPM on a Brookfield DV-III cone and plate viscometer equipped with a #CP-52 spindle. A method for preparing a wood-plastic composite article from the composition is also disclosed.
[0005] The solid carrier component is (i) as starting material (c), the polydiorganosiloxane described above; (ii) ethylene-based polymers, Maleated ethylene-based polymers, and A combination of both an ethylene-based polymer and a maleated ethylene-based polymer; A polymer component selected from the group consisting of and A solid carrier component can be useful in providing the polydiorganosiloxane to the composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0006] The above compositions are useful in the preparation of wood-plastic composite articles. 15% by weight to 70% by weight of (a) a lignocellulosic filler; 29.5% by weight to 84.5% by weight of (b) an ethylene-based polymer; 0.5% to 6% by weight of (c) unit formula: (R2R'SiO 1 / 2 ) a (R3SiO 1 / 2 ) b (R2SiO 2 / 2 ) c (RR'SiO 2 / 2 ) d wherein each R is an independently selected monovalent hydrocarbon radical of 1 to 18 carbon atoms free of aliphatic unsaturation; each R' is an independently selected alkenyl radical of 2 to 18 carbon atoms; subscript a is 0 to 2, subscript b is 0 to 2, the sum (a+b)=2, subscript c is 0 or greater, subscript d is 0 or greater, the sum (a+d)≧1, and the sum (a+b+c+d) is sufficient to impart to the polydiorganosiloxane a viscosity of 2,000 mPa·s to 60,000 mPa·s when measured at 25° C. and 0.1 to 50 RPM on a Brookfield DV-III cone and plate viscometer equipped with a #CP-52 spindle. and 0 to 4 weight percent of (d) a maleated ethylene-based polymer; It may include, Each is based on the combined weight of starting materials (a), (b), (c), and (d) in the composition.
[0007] (a) Lignocellulosic filler The composition includes a starting material (a) a lignocellulosic filler. The lignocellulosic filler comprises, consists essentially of, or consists of lignocellulosic material. Typically, the lignocellulosic filler consists of lignocellulosic material. The lignocellulosic filler, as well as the lignocellulosic material, may include any material derived from any plant source. When the lignocellulosic filler consists essentially of or consists of lignocellulosic material, the lignocellulosic material may also include some water or moisture, although the lignocellulosic material, as well as the lignocellulosic filler, are typically dry, i.e., do not contain any free moisture other than that which may be related to the relative humidity in the environment in which the lignocellulosic filler is prepared, derived, formed, and / or stored. The same is generally true for (a) other types of lignocellulosic fillers, although care must be taken with respect to lignocellulosic fillers since lignocellulosic materials generally contain some moisture when recovered / prepared prior to any drying or end use.
[0008] Lignocellulosic fillers typically include carbohydrate polymers (e.g., cellulose and / or hemicellulose) and may further include aromatic polymers (e.g., lignin). Lignocellulosic fillers are typically natural lignocellulosic materials, i.e., not synthetically derived. For example, lignocellulosic fillers are typically derived from wood (hardwood, softwood, and / or plywood). Alternatively, or in addition, lignocellulosic fillers may include lignocellulosic materials from other non-wood sources, such as plant-derived lignocellulosic materials, or other plant-derived polymers, such as agricultural by-products, grain husks, sisal, bagasse, wheat straw, kapok, ramie, heneques, corn fiber or coir, nut shells, flax, jute, hemp, kenaf, rice husks, abaca, peanut husks, bamboo, straw, lignin, starch, or cellulose and cellulose-containing products, and combinations thereof. The lignocellulosic filler may be virgin, recycled, or a combination thereof.
[0009] Alternatively, the lignocellulosic filler may comprise a wood filler. "Wood" is as described in The Chemical Composition of Wood by Pettersen, Roger C., USDepartment of Agriculture, Forest Service, Forest Products Laboratory, Madison, WI, Chapter 2. Wood may contain lignin in an amount of 18% to 35%, carbohydrates in an amount of 65% to 75%, and possibly inorganic minerals in an amount of up to 10%. The carbohydrate portion of wood includes cellulose and hemicellulose. The cellulose content may range from 40% to 50% of the dry wood weight, and the hemicellulose may range from 25% to 35%. The α-cellulose content may be 29% to 57%, alternatively 40% to 50%, based on the dry weight of the wood filler. The wood filler is derived from wood, e.g., hardwood and / or softwood. Specific examples of suitable hardwoods from which the wood filler may be derived include, but are not limited to, ash, aspen, cottonwood, linden, birch, beech, chestnut, gum, elm, eucalyptus, maple, oak, poplar, sycamore, and combinations thereof. Specific examples of suitable softwoods from which the wood filler may be derived include, but are not limited to, spruce, fir, hemlock, tamarack, larch, pine, cypress, sequoia, and combinations thereof. Fillers derived from combinations of different hardwoods, combinations of different softwoods, or combinations of hardwood(s) and softwood(s) may be used together as wood fillers. Alternatively, the lignocellulosic filler may consist essentially of wood fillers. Alternatively, the lignocellulosic filler may consist of wood fillers.
[0010] The lignocellulosic filler may have any form and size, for example, a particle size from nanometers to millimeters. For example, the lignocellulosic filler may include powder, pulp, flour, sawdust, fiber, flakes, chips, shavings, strands, scrims, wafers, wool, straw, particles, or any combination thereof. The lignocellulosic filler may be formed, typically based on its form, through various techniques known to those skilled in the art. For example, the lignocellulosic filler may be prepared by grinding logs, branches, industrial wood residues, or crude pulp wood. The lignocellulosic filler may be ground to a desired particle size. For example, the lignocellulosic filler may be ground in any convenient device, such as a hammer mill, resulting in a lignocellulosic filler having a particle size suitable for use in the mixing process. The desired particle size is typically selected by those skilled in the art based on the particular mixing process utilized and the desired properties of the wood-plastic composite article. Particle size refers to the dimensions of the lignocellulosic filler regardless of shape, including, for example, the dimensions associated with the lignocellulosic filler when in the form of fibers. As is known in the art, the lignocellulosic filler may be pelletized or in the form of pellets, which may substantially maintain their shape and size when incorporated into the composition, or may form smaller particles in the composition.
[0011] The shape and size of the lignocellulosic filler are also not particularly limited. For example, the lignocellulosic filler may be spherical, rectangular, ovoid, irregular, and may be in the form of, for example, powder, dust, fibers, flakes, chips, shavings, strands, scrims, wafers, wool, straw, particles, and combinations thereof. The size and shape are typically selected based on the type of lignocellulosic filler utilized, the selection of other starting materials included in the WPC composition, and the end use of the WPC article formed therewith.
[0012] Starting material (a) may be one lignocellulosic filler or a combination of two or more lignocellulosic polymers that differ from each other in at least one property, such as the plant source from which the lignocellulosic filler is derived, the lignin content, the α-cellulose content, the preparation method, the filler shape, the filler surface area, the particle size distribution, and / or the particle size distribution. Starting material (a) may be present in the composition in an amount of 15% to 70%, alternatively 40% to 70%, alternatively 45% to 65%, based on the combined weight of starting materials (a), (b), (c), and (d).
[0013] (b) Ethylene-based polymer The above composition further comprises starting material (b) an ethylene-based polymer. As used herein, an "ethylene-based" polymer is a polymer prepared from ethylene monomer as the major (i.e., greater than 50%) monomer component, although other comonomers may also be used. "Polymer" refers to a polymeric compound prepared by reacting (i.e., polymerizing) monomers of the same or different types, including homopolymers and interpolymers. "Interpolymer" refers to a polymer prepared by polymerization of at least two different monomer types. This general term includes copolymers (usually used to refer to polymers prepared from two different monomer types) and polymers prepared from more than two different monomer types, such as terpolymers (three different monomer types) and tetrapolymers (four different monomer types).
[0014] The ethylene-based polymer may be an ethylene homopolymer. As used herein, "homopolymer" means a polymer that contains repeat units derived from a single monomer type, but does not exclude residual amounts of other components used in preparing the homopolymer, such as catalysts, initiators, solvents, and chain transfer agents.
[0015] Alternatively, the ethylene-based polymer may be an ethylene / alpha-olefin ("α-olefin") interpolymer having an α-olefin content of at least 1%, alternatively at least 5%, alternatively at least 10%, alternatively at least 15%, alternatively at least 20%, alternatively at least 25% by weight, based on the total weight of the interpolymer. These interpolymers may have an α-olefin content of less than 50%, alternatively less than 45%, alternatively less than 40%, alternatively less than 35%, based on the total weight of the interpolymer. When an α-olefin is used, the α-olefin may have from 3 to 20 carbon atoms (C3-C20) and may be a linear, branched, or cyclic α-olefin. Examples of C3-20 α-olefins include propene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, and 1-octadecene. The α-olefins can also have cyclic structures such as cyclohexane or cyclopentane, resulting in α-olefins such as 3-cyclohexyl-1-propene (allylcyclohexane) and vinylcyclohexane. Exemplary ethylene / α-olefin interpolymers include ethylene / propylene, ethylene / 1-butene, ethylene / 1-hexene, ethylene / 1-octene, ethylene / propylene / 1-octene, ethylene / propylene / 1-butene, and ethylene / 1-butene / 1-octene.
[0016] Starting material (b) may be an ethylene-based polymer or a combination of two or more ethylene-based polymers (e.g., a blend of two or more ethylene-based polymers that differ from each other in at least one property, such as monomer composition, monomer content, catalyst preparation method, molecular weight, molecular weight distribution, and / or density). When a blend of ethylene-based polymers is used, the polymers can be blended by any in-reactor or post-reactor process.
[0017] The ethylene-based polymer starting material (b) may be selected from the group consisting of high density polyethylene (HDPE), medium density polyethylene (MDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), low density low molecular weight polyethylene (LDLMWPE), and combinations thereof.
[0018] Alternatively, starting material (b) may be LLDPE. LLDPE is generally an ethylene-based polymer having a non-uniform distribution of comonomers (e.g., α-olefin monomers) and characterized by short chain branching. For example, the LLDPE may be a copolymer of ethylene and α-olefin monomers such as those listed above. LLDPE has a viscosity of 0.91 g / cm 3 ~0.94g / cm 3 The density of the LLDPE and other ethylene-based polymers described herein is determined by ASTM D792-13. The LLDPE suitable for use herein may have a melt index (I2) of from 1 g / 10 min to 20 g / 10 min, alternatively from greater than 2 g / 10 min, alternatively from 2.3 g / 10 min to 20 g / 10 min, alternatively from 2.3 g / 10 min to 12 g / 10 min, alternatively from 2.3 g / 10 min to 6 g / 10 min, alternatively from 4.4 g / 10 min to 20 g / 10 min, alternatively from 6.8 g / 10 min to 20 g / 10 min. The I2 values of the LLDPE and other ethylene-based polymers are determined according to ASTM D1238-13 at 190°C and 2.16 Kg. The LLDPE may have a melting temperature of at least 124°C, alternatively from 124°C to 135°C, alternatively from 124°C to 132°C. The melting temperature of LLDPE and other polyethylene-based polymers is determined by DSC according to ASTM D3418-15.
[0019] LLDPEs are known in the art and may be produced by known methods. For example, LLDPEs may be made using Ziegler-Natta catalyst systems, as well as single-site catalysts such as bis-metallocenes (sometimes referred to as "m-LLDPEs"), post-metallocene catalysts, and constrained geometry catalysts. LLDPEs include linear, substantially linear, or heterogeneous polyethylene copolymers or homopolymers. LLDPEs may contain less long chain branching than LDPEs, and include substantially linear ethylene polymers as further defined in U.S. Pat. Nos. 5,272,236, 5,278,272, and 5,582,923, homogeneously branched linear ethylene polymer compositions such as those in U.S. Pat. No. 3,645,992, and / or heterogeneously branched ethylene polymers such as those prepared according to the process disclosed in U.S. Pat. No. 4,076,698. LLDPE can be produced by gas phase, liquid phase, or slurry polymerization, or any combination thereof, using any type of reactor or reactor configuration known in the art.
[0020] Alternatively, the ethylene-based polymer may be MDPE. MDPE has a viscosity of approximately 0.926 g / cm 3 ~0.940g / cm 3 Alternatively, MDPE is an ethylene-based polymer having a density in the range of 0.930 g / cm 3 ~0.939g / cm 3The MDPE may have an I2 of 0.1 g / 10 min to 20 g / 10 min, alternatively greater than 2 g / 10 min, alternatively 2.3 g / 10 min to 20 g / 10 min, alternatively 2.3 g / 10 min to 12 g / 10 min, alternatively 2.3 g / 10 min to 6 g / 10 min, alternatively 4.4 g / 10 min to 20 g / 10 min, alternatively 6.8 g / 10 min to 20 g / 10 min. The MDPE may have a melt temperature of at least 124°C, alternatively 124°C to 135°C, alternatively 124°C to 132°C. The MDPE may be produced using chromium or Ziegler-Natta catalysts, or using metallocene, constrained geometry, or single site catalysts, and typically has an MWD greater than 2.5.
[0021] Alternatively, the ethylene-based polymer may be HDPE. HDPE has a viscosity of at least 0.940 g / cm 3 Alternatively, HDPE is an ethylene-based polymer having a density of 0.940 g / cm 3 Super~0.970g / cm 3 , or 0.940 g / cm 3 Super~0.965g / cm 3 , or over 0.940 to 0.952 g / cm 3 The HDPE may have a melting temperature of at least 124°C, alternatively from 124°C to 135°C, alternatively from 124°C to 132°C, alternatively from 131°C to 132°C. The HDPE may have an I2 of 0.1g / 10min to 66g / 10min, alternatively from 0.2g / 10min to 20g / 10min, alternatively from greater than 2g / 10min, alternatively from 2.3g / 10min to 20g / 10min, alternatively from 3g / 10min to 12g / 10min, alternatively from 4g / 10min to 7g / 10min, alternatively from 4.4g / 10min to 20g / 10min, alternatively from 6.8g / 10min to 20g / 10min. The HDPE may have a PDI as measured by GPC of 1.0 to 30.0, alternatively from 2.0 to 15.0.
[0022] The HDPE suitable for use herein may be unimodal. As used herein, "unimodal" means an HDPE having an MWD whose GPC curve shows only a single peak, without a discernible second peak, or even without a shoulder-like or ridge-like peak relative to such single peak. In contrast, "bimodal" means that the MWD in the GPC curve shows the presence of two component polymers, such as by having two peaks, or when one component is shown by a ridge, shoulder-like or tail-like peak relative to the peak of the other component polymer. The HDPE used herein may be unimodal. Unimodal HDPE is commercially available from The Dow Chemical Company (Midland, MI, USA). HDPE is known in the art and can be produced by known methods. For example, HDPE can be prepared using Ziegler-Natta catalysts, chromium catalysts, or even metallocene catalysts.
[0023] Alternatively, the ethylene-based polymer of the starting material (b) may be selected from the group consisting of HDPE, MDPE, LLDPE, and combinations thereof. Alternatively, the ethylene-based polymer of the starting material (b) may be selected from the group consisting of HDPE, LLDPE, and combinations thereof. Alternatively, the ethylene-based polymer of the starting material (b) may be selected from the group consisting of HDPE and LLDPE. Methods for preparing ethylene-based polymers are well known in the art. Any known or hereafter discovered method for preparing ethylene-based polymers having the desired properties may be used to produce the ethylene-based polymers. Suitable LLDPE, MDPE, and HDPE can be prepared by the methods described above or methods disclosed in PCT Publication No. WO 2018 / 049555 and US Patent Publication No. 2019 / 0023895 and references cited therein. Suitable ethylene-based polymers are commercially available from The Dow Chemical Company (Midland, MI, USA), and examples are shown in Table 1 below. [Table 1]
[0024] The ethylene-based polymer for use in the composition may comprise virgin polymer and / or recycled polymer. Without being bound by theory, it is believed that the ethylene-based polymer may comprise 50% or more recycled polyethylene. The recycled ethylene-based polymer, if utilized, may be sourced from industrial production streams and from post-industrial and / or post-consumer sources. The selection of a particular ethylene-based polymer and any ratio of virgin polymer to recycled polymer, if utilized at the same time, typically depends on the cost and desired properties of the WPC article formed therewith.
[0025] Starting material (b) may be present in the composition in an amount from 29.5% to 84.5%, alternatively from 30% to 60%, alternatively from 35% to 55%, alternatively from 40% to 50%, based on the combined weight of starting materials (a), (b), (c), and (d).
[0026] (c) Polydiorganosiloxane The above composition further comprises starting material (c), a polydiorganosiloxane having at least one silicon-bonded alkenyl group per molecule. The polydiorganosiloxane has the unit formula: (R2R'SiO 1 / 2 ) a (R3SiO 1 / 2 ) b (R2SiO 2 / 2 ) c (RR'SiO 2 / 2 ) d wherein each R is an independently selected monovalent hydrocarbon radical of 1 to 18 carbon atoms free of aliphatic unsaturation; each R' is an independently selected alkenyl radical of 2 to 18 carbon atoms; subscript a is 0 to 2, subscript b is 0 to 2, the sum (a+b)=2, subscript c is 0 or greater, subscript d is 0 or greater, the sum (a+d)≧1, and the sum (a+b+c+d) is sufficient to impart to the polydiorganosiloxane a viscosity of 2,000 mPa·s to 60,000 mPa·s when measured at 25° C. and 0.1 to 50 RPM on a Brookfield DV-III cone and plate viscometer equipped with a #CP-52 spindle. A person skilled in the art will recognize that when using this test method to measure viscosity, the rotation speed decreases as the viscosity increases, and that an appropriate rotation speed can be selected. Alternatively, the viscosity can be from 2,000 mPa·s to 10,000 mPa·s, alternatively from 2,000 mPa·s to 5,000 mPa·s, when measured at 5 RPM according to the test method described above. Alternatively, the subscript d can be from 0 to 4, alternatively from 1 to 4, alternatively from 1 to 3, alternatively from 2. Alternatively, the sum (a+d) can be sufficient to provide an amount of alkenyl groups R' of 0.05% to 7%, alternatively from 0.09% to 6.5%, based on the weight of the polydiorganosiloxane. The vinyl content can be measured by FTIR.
[0027] Alternatively, in the polydiorganosiloxane unit formula above, each R may be an alkyl group of 1 to 18 carbon atoms, alternatively 1 to 12 carbon atoms, alternatively 1 to 6 carbon atoms, alternatively 1 to 4 carbon atoms. Suitable alkyl groups include methyl, ethyl, propyl (including n-propyl and isopropyl), and butyl (including n-butyl, tert-butyl, sec-butyl, and iso-butyl). Alternatively, each R may be methyl.
[0028] Alternatively, in the polydiorganosiloxane formula above, each R' may be an alkenyl group of 2 to 12 carbon atoms, alternatively 2 to 6 carbon atoms, alternatively 2 to 4 carbon atoms. Suitable alkenyl groups include vinyl, allyl, butenyl, and hexenyl. Alternatively, each R' may be vinyl or hexenyl. Alternatively, each R' may be vinyl.
[0029] The polydiorganosiloxane may have terminal alkenyl groups, pendant alkenyl groups, or both terminal and pendant alkenyl groups. Alternatively, in the polydiorganosiloxane formula, subscript a may be 0 and subscript d may be 1 or greater, i.e., the polydiorganosiloxane may have pendant alkenyl groups but not terminal alkenyl groups. Alternatively, subscript a may be 2, subscript b may be 0, and subscript d may be 0, i.e., the polydiorganosiloxane may be a bis-alkenyl terminated polydiorganosiloxane.
[0030] The bis-alkenyl terminated polydiorganosiloxane has the formula [ka] where each R and R' is as described above and the subscript x has a value sufficient to provide the polydiorganosiloxane with a viscosity that is from 2,000 mPa·s to 60,000 mPa·s when measured as described above. Those skilled in the art will recognize that when using this test method to measure viscosity, the rotation speed decreases as the viscosity increases and can select an appropriate rotation speed. Alternatively, the viscosity can be from 2,000 mPa·s to 10,000 mPa·s, or from 2,000 mPa·s to 5,000 mPa·s when measured at 5 RPM according to the test method described above.
[0031] Alternatively, each R may be an alkyl group of 1 to 18 carbon atoms, alternatively 1 to 12 carbon atoms, alternatively 1 to 6 carbon atoms, alternatively 1 to 4 carbon atoms. Suitable alkyl groups include methyl, ethyl, propyl (including n-propyl and isopropyl), and butyl (including n-butyl, tert-butyl, sec-butyl, and iso-butyl). Alternatively, each R may be methyl.
[0032] Alternatively, in the polydiorganosiloxane formula above, each R' may be an alkenyl group of 2 to 12 carbon atoms, alternatively 2 to 6 carbon atoms, alternatively 2 to 4 carbon atoms. Suitable alkenyl groups include vinyl, allyl, butenyl, and hexenyl. Alternatively, each R' may be vinyl or hexenyl. Alternatively, each R' may be vinyl.
[0033] The starting material (c) is c-1) α,ω-dimethylvinylsiloxy-terminated polydimethylsiloxane, c-2) α,ω-dimethylvinylsiloxy-terminated poly(dimethylsiloxane / methylphenylsiloxane), c-3) α,ω-dimethylvinylsiloxy-terminated poly(dimethylsiloxane / diphenylsiloxane), c-4) α,ω-phenyl, methyl, vinyl-siloxy terminated polydimethylsiloxane, c-5) α,ω-dimethylhexenylsiloxy-terminated polydimethylsiloxane, c-6) α,ω-dimethylhexenylsiloxy-terminated poly(dimethylsiloxane / methylphenylsiloxane), c-7) α,ω-dimethylhexenylsiloxy-terminated poly(dimethylsiloxane / diphenylsiloxane), c-8) α,ω-phenyl, methyl, hexenyl-siloxy terminated polydimethylsiloxane, c-9) α,ω-dimethylvinylsiloxy-terminated poly(dimethylsiloxane / methylvinylsiloxane), c-10) α,ω-dimethylvinylsiloxy-terminated poly(dimethylsiloxane / methylphenylsiloxane / methylvinylsiloxane), c-11) α,ω-dimethylvinylsiloxy-terminated poly(dimethylsiloxane / diphenylsiloxane / methylvinylsiloxane), c-12) α,ω-phenyl, methyl, vinyl-siloxy terminated poly(dimethylsiloxane / methylvinylsiloxane), c-13) α,ω-dimethylhexenylsiloxy-terminated poly(dimethylsiloxane / methylhexenylsiloxane), c-14) α,ω-dimethylhexenylsiloxy-terminated poly(dimethylsiloxane / methylphenylsiloxane / methylhexenylsiloxane), c-15) α,ω-dimethylhexenylsiloxy-terminated poly(dimethylsiloxane / diphenylsiloxane / methylhexenylsiloxane), c-16) α,ω-phenyl, methyl, hexenyl-siloxy terminated poly(dimethylsiloxane / methylhexenylsiloxane), c-17) trimethylsiloxy-terminated poly(dimethylsiloxane / methylvinylsiloxane), c-18) Trimethylsiloxy-terminated poly(dimethylsiloxane / methylphenylsiloxane / methylvinylsiloxane), c-19) Trimethylsiloxy-terminated poly(dimethylsiloxane / diphenylsiloxane / methylvinylsiloxane), c-20) trimethylsiloxy-terminated poly(dimethylsiloxane / methylhexenylsiloxane), c-21) Trimethylsiloxy-terminated poly(dimethylsiloxane / methylphenylsiloxane / methylhexenylsiloxane), c-22) Trimethylsiloxy-terminated poly(dimethylsiloxane / diphenylsiloxane / methylhexenylsiloxane), c-23) A combination of two or more of c-1) to c-22); Alternatively, the polydiorganosiloxane may be selected from the group consisting of c-1), c-5), c-9), c-13), c-17), c-20), and combinations of two or more thereof. Alternatively, the polydiorganosiloxane may be selected from the group consisting of c-1), c-5), c-9), c-13), and combinations of two or more thereof. Alternatively, the polydiorganosiloxane may be a bis-vinyldimethylsiloxy terminated polydimethylsiloxane. The above polydiorganosiloxanes are commercially available. Bis-vinyldimethylsiloxy terminated polydimethylsiloxanes are commercially available from Dow Silicones Corporation (Midland, Michigan, USA) and examples include bis-vinyldimethylsiloxy terminated polydimethylsiloxane with a viscosity of 60,000 mPa·s, bis-vinyldimethylsiloxy terminated polydimethylsiloxane with a viscosity of 10,000 mPa·s, bis-vinyldimethylsiloxy terminated polydimethylsiloxane with a viscosity of 5,000 mPa·s, and bis-vinyldimethylsiloxy terminated polydimethylsiloxane with a viscosity of 2,000 mPa·s, as measured at 25° C. and 0.1 to 50 RPM using a Brookfield DV-III cone and plate viscometer equipped with a #CP-52 spindle. Suitable polydiorganosiloxanes can be prepared by methods known in the art such as the hydrolysis and condensation of appropriate organohalosilane monomers and / or the equilibration reaction of linear and cyclic polyorganosiloxanes, optionally with end-capping.
[0034] Starting material (c) may be one polydiorganosiloxane or a combination of two or more polydiorganosiloxanes that differ from one another in at least one property, such as the selection of R groups, the selection of R' groups, and viscosity. Starting material (c) may be present in the composition in an amount of from 0.5% to 6%, alternatively from 1% to 4%, alternatively from 0.5% to 3%, alternatively from 1% to 2%, alternatively from 1.5% to 2%, based on the combined weight of starting materials (a), (b), (c), and (d).
[0035] (d) Maleated ethylene polymers The above composition may further comprise starting material (d) maleated ethylene-based polymer. As used herein, the term "maleated" refers to a polymer (e.g., an ethylene-based polymer) that has been modified to incorporate maleic anhydride monomer. Maleic anhydride can be incorporated into an ethylene-based polymer by any method known in the art or hereafter discovered. For example, maleic anhydride can be copolymerized with ethylene and other monomers (if present) to prepare an interpolymer having maleic anhydride residues incorporated into the polymer backbone. Alternatively, maleic anhydride can be graft polymerized onto an ethylene-based polymer. Techniques for copolymerization and graft polymerization are known in the art.
[0036] The maleated ethylene-based polymer may be an ethylene-based polymer having maleic anhydride grafted onto the polymer. The ethylene-based polymer before maleation may be any of the ethylene-based polymers listed above, or alternatively, the ethylene-based polymer used for maleation may have a melt index lower than the melt index of the ethylene-based polymers listed above. The ethylene-based starting polymer may be selected from linear low density polyethylene, medium density polyethylene, and high density polyethylene. Alternatively, the starting ethylene-based polymer may be high density polyethylene.
[0037] The maleated ethylene-based polymer has a viscosity of at least 0.923 g / cm 3 Alternatively, the maleated ethylene-based polymer may have a density of 0.923 g / cm 3 ~0.962g / cm 3 , or 0.940 g / cm 3 ~0.962g / cm 3 , or 0.923 g / cm 3 ~0.940g / cm 3The density of the maleated ethylene-based polymer may be determined by ASTM D792-13. The maleated ethylene-based polymer may have an I2 of 0.1 g / 10 min to 25 g / 10 min, alternatively 0.1 g / 10 min to 10 g / 10 min, alternatively 1 g / 10 min to 2 g / 10 min, alternatively 2 g / 10 min to 25 g / 10 min, alternatively 2 g / 10 min to 12 g / 10 min, alternatively 3 g / 10 min to 25 g / 10 min, alternatively 3 g / 10 min to 12 g / 10 min. The I2 value of the maleated ethylene-based polymer is determined at 190° C. and 2.16 Kg according to ASTM D1238-13. The maleated ethylene-based polymer may have a maleic anhydride content of at least 0.25%, alternatively 0.25% to 2.5%, alternatively 0.5% to 1.5%, based on the total weight of the maleated ethylene-based polymer. The maleic anhydride concentration may be measured by a titration method in which the dried resin is titrated with 0.02N KOH to determine the amount of maleic anhydride. The dried polymer is titrated by dissolving 0.3 to 0.5 grams of the maleated ethylene-based polymer in 150 mL of refluxing xylene. After complete dissolution, deionized water (4 drops) is added to the solution and the solution is refluxed for 1 hour. 1% thymol blue (a few drops) is then added to the solution and the solution is overtitrated with 0.02N KOH ethanol solution as indicated by the production of a purple color. The solution is then back-titrated with 0.05N HCl isopropanol solution to a yellow endpoint.
[0038] Maleated ethylene-based polymers suitable for starting material (d) can be prepared by known methods such as those disclosed in PCT Publication WO 2018 / 049555 and the references cited therein. Alternatively, maleated ethylene-based polymers can be prepared by a process of grafting maleic anhydride onto an ethylene-based polymer, which can be initiated by decomposing initiators such as azo-containing compounds, carboxylic acid peroxy acids and peroxy esters, alkyl hydroperoxides, and dialkyl and diacyl peroxides, among others, to form free radicals. Many of these compounds and their properties have been described (Reference: J. Branderup, E. Immergut, E. Grulke, eds. "Polymer Handbook," 4th ed., Wiley, New York, 1999, Section II, pp. 1-76.). Alternatively, the molecular species formed by decomposition of the initiator can be oxygen-based free radicals. Alternatively, the initiator may be selected from the group consisting of carboxylic acid peroxyesters, peroxyketals, dialkyl peroxides, and diacyl peroxides. Exemplary initiators commonly used to modify the structure of polymers are listed in the table at column 48, line 13 to column 49, line 29 of U.S. Pat. No. 7,897,689. Alternatively, the grafting process for producing maleated ethylene-based polymers can be initiated by free radicals generated by a thermal oxidation process. Suitable maleated ethylene-based polymers are commercially available from The Dow Chemical Company (Midland, MI, USA), such as those listed in Table 2 below. [Table 2]
[0039] In table (d), density was measured by ASTM D792-13, I2 value was measured by ASTM D1238-13 at 190°C and 2.16 Kg, and melt temperature was measured by DSC according to ASTM D3418-15.
[0040] Starting material (d) may be one maleated ethylene-based polymer or a combination of two or more maleated ethylene-based polymers (e.g., a blend of two or more maleated ethylene-based polymers that differ from each other in at least one property, such as monomer composition, monomer content, catalyst preparation method, molecular weight, molecular weight distribution, and / or density). The maleated ethylene-based polymer may be present in the composition in an amount of 0-4%. Alternatively, the maleated ethylene-based polymer may be present in an amount of 0-2%, alternatively greater than 0% to 2%, alternatively 1% to 3%, alternatively 1% to 2%, based on the combined weight of starting materials (a), (b), (c), and (d).
[0041] Additional Starting Materials The composition may optionally further comprise one or more additional starting materials. For example, the one or more additional starting materials may be selected from the group consisting of (e) an additional filler different from the lignocellulosic filler of starting material (a), (f) a colorant, (g) a foaming agent, (h) a UV stabilizer, (i) an antioxidant, (j) a processing aid, (k) a preservative, (l) a biocide, (m) a flame retardant, (n) an impact modifier, and (o) a combination of two or more starting materials (e)-(n). Each additional starting material, if utilized, may be present in the composition in an amount of greater than 0-30%, based on the total weight of all starting materials in the composition. The composition may include other optional additives as known in the art. Such additives are described, for example, in Walker, Benjamin M., and Charles P. Rader, eds. Handbook of thermoplastic elastomers. New York: Van Nostrand Reinhold, 1979; Murphy, John, ed. Additives for plastics handbook. Elsevier, 2001.
[0042] (e) Additional fillers The composition may optionally further comprise starting material (e) fillers different from the lignocellulosic fillers described above as starting material (a). Specific examples of suitable fillers include, but are not limited to, calcium carbonate, silica, quartz, fused quartz, talc, mica, clay, kaolin, wollastonite, feldspar, aluminum hydroxide, carbon black, and graphite. Alternatively, the filler may be a mineral filler. Alternatively, the filler may be selected from the group consisting of calcium carbonate, talc, and combinations thereof. Suitable fillers are known in the art and commercially available, for example crushed silica sold under the name MIN-U-SIL by US Silica (Berkeley Springs, West Virginia, USA). Suitable precipitated calcium carbonates include Winnofil™ SPM from Solvay, and Ultra-pflex™ and Ultra-pflex™ 100 from Specialty Minerals (Quinnesec, Michigan, USA).
[0043] The shape and size of the filler are not particularly limited.For example, the filler may be spherical, rectangular, oval, irregular, and may be in the form of, for example, powder, powder, fiber, flake, chip, shavings, strand, scrim, wafer, wool, straw, particles, and combinations thereof.The size and shape are typically selected based on the type of filler utilized and the selection of other starting materials included in the solid carrier component.
[0044] Regardless of the choice of filler, the filler may be untreated, pretreated, or added in combination with any filler treating agent described below, and if added in combination, the filler may be treated in situ or prior to incorporation of the filler into the composition. Alternatively, the filler may be surface treated to facilitate wetting or dispersion in the composition, and if so added, such fillers may be treated in situ in the composition.
[0045] The filler treating agent may include a silane such as an alkoxysilane, an alkoxy-functional oligosiloxane, a cyclic polyorganosiloxane, a hydroxyl-functional oligosiloxane such as dimethylsiloxane or methylphenylsiloxane, an organosilicon compound, stearic acid, or a fatty acid. The filler treating agent may include a single filler treating agent or may include a combination of two or more filler treating agents selected from similar or different types of molecules.
[0046] The filler treating agent may include an alkoxysilane, which may be a monoalkoxysilane, a di-alkoxysilane, a tri-alkoxysilane, or a tetraalkoxysilane. Examples of alkoxysilane filler treating agents include hexyltrimethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, dodecyltrimethoxysilane, tetradecyltrimethoxysilane, phenyltrimethoxysilane, phenylethyltrimethoxysilane, octadecyltrimethoxysilane, octadecyltriethoxysilane, and combinations thereof. In certain embodiments, the alkoxysilane may be used in combination with a silazane that catalyzes the reaction of the less reactive alkoxysilane with the surface hydroxyl. Such reactions are typically carried out at temperatures above 100°C, with high shear, and with removal of volatile by-products such as ammonia, methanol, and water.
[0047] Suitable filler treating agents include alkoxysilyl-functional alkylmethylpolysiloxanes or similar materials in which the hydrolyzable groups can include, for example, silazane, acyloxy, or oximo.
[0048] Alkoxy-functional oligosiloxanes can also be used as filler treating agents.Alkoxy-functional oligosiloxanes and their preparation methods are generally known in the art.Other filler treating agents include mono-endblocked alkoxy-functional polydiorganosiloxanes, i.e., polyorganosiloxanes with alkoxy functionality at one end.
[0049] Alternatively, filler treating agent can be any of the organosilicon compounds commonly used for treating silica fillers.The examples of organosilicon compounds include organochlorosilanes such as methyltrichlorosilane, dimethyldichlorosilane and trimethylmonochlorosilane; organosiloxanes such as hydroxyl endblocked dimethylsiloxane oligomers, silicon hydride functional siloxanes, hexamethyldisiloxane and tetramethyldivinyldisiloxane; organosilazanes such as hexamethyldisilazane and hexamethylcyclotrisilazane; and organoalkoxysilanes such as alkylalkoxysilanes with methyl, propyl, n-butyl, i-butyl, n-hexyl, n-octyl, i-octyl, n-decyl, dodecyl, tetradecyl, hexadecyl or octadecyl substituents. The organic reactive alkoxysilanes may include amino, methacryloxy, vinyl, glycidoxy, epoxycyclohexyl, isocyanurate, isocyanato, mercapto, sulfide, vinyl-benzyl-amino, benzyl-amino, or phenyl-amino substituents. Alternatively, the filler treating agent may include an organopolysiloxane. Alternatively, certain filler treating agents, such as chlorosilanes, may be hydrolyzed at the filler surface. Alternatively, the filler treating agent may utilize multiple hydrogen bonds, either clustered or dispersed, or both, as a method of bonding the organosiloxane to the filler surface. The hydrogen-bondable organosiloxane has, on average, at least one silicon-bonded group capable of hydrogen bonding per molecule. The group may be selected from monovalent organic groups with multiple hydroxyl functionality or monovalent organic groups with at least one amino functionality. Hydrogen bonding may be the primary mode of attachment of the organosiloxane to the filler. The organosiloxane may not be capable of forming a covalent bond with the filler. The hydrogen-bondable organosiloxane may be selected from the group consisting of sugar-siloxane polymers, amino-functional organosiloxanes, and combinations thereof. Alternatively, the hydrogen-bondable polyorganosiloxane may be a sugar-siloxane polymer.
[0050] Alternatively, the filler treating agent may include alkyl thiols, such as octadecyl mercaptan, and fatty acids, such as oleic acid, stearic acid, titanates, titanate coupling agents, zirconate coupling agents, and combinations thereof. One of ordinary skill in the art would be able to optimize the filler treating agent to aid in the dispersion of the filler without undue experimentation.
[0051] Starting material (e) may be one additional filler or a combination of two or more additional fillers that differ from each other in at least one property, such as filler type, preparation method, treatment or surface chemistry, filler composition, filler shape, filler surface area, average particle size, and / or particle size distribution, etc. Additional fillers, when present, may be added to the composition in an amount of greater than 0% to 30%, alternatively 10% to 15%, based on the total weight of all starting materials in the composition.
[0052] When selecting starting materials to be included in the composition, the types of starting materials may overlap, since a particular starting material described herein may have more than one function. For example, (e) additional filler may be useful as additional filler, colorant, and even flame retardant (e.g., carbon black). When selecting starting materials for the composition, the selected components are different from each other.
[0053] Manufacturing method The present invention further relates to a method for preparing a wood plastic composite (WPC) article, the method comprising: 1) 15% by weight to 70% by weight of (a) the above lignocellulosic filler; 29.5% by weight to 84.5% by weight of (b) the ethylene-based polymer; 0.5% by weight to 6% by weight of (c) unit formula (R2R'SiO 1 / 2 ) a (R3SiO 1 / 2 ) b (R2SiO 2 / 2 ) c (RR'SiO 2 / 2 ) d where R and R', and subscripts a, b, c, and d are as defined above. and 0 to 4% by weight of (D) a maleated ethylene-based polymer; Combining starting materials comprising: combining starting materials (a), (b), (c), and (d), respectively, thereby preparing a composition; 2) forming a WPC article from the composition.
[0054] In step (1), the composition is formed by combining at least (a) a lignocellulosic filler, (b) an ethylene-based polymer, and (c) a polydiorganosiloxane, along with any optional starting materials present in the composition. When (c) the polydiorganosiloxane is in the form of a solid support component, the method may include combining (a) the lignocellulosic filler with (b) the ethylene-based polymer, and (c) a solid support component comprising the polydiorganosiloxane.
[0055] The starting materials of the composition may be combined in any order and in any suitable manner. For example, the (b) ethylene-based polymer may be melted before, during, and / or after forming the composition. For example, the (b) ethylene-based polymer may be heated before and / or during the combination of the starting materials, such that the (a) lignocellulosic filler and (c) polydiorganosiloxane are combined with the molten form of the (b) ethylene-based polymer. The starting materials (a) lignocellulosic filler and (c) polydiorganosiloxane are combined with the molten form of the (b) ethylene-based polymer, for example, individually, sequentially, together, or simultaneously. However, alternatively, the (b) ethylene-based polymer may be combined with the (a) lignocellulosic filler and (c) polydiorganosiloxane before heating or melting the starting materials (b) ethylene-based polymer, such that the (b) ethylene-based polymer is in a solid and non-molten or non-softened form when preparing the composition. Alternatively, (a) the lignocellulosic filler and (c) the polydiorganosiloxane may be combined and heated, and then (b) the ethylene-based polymer may be added in solid or liquid form when preparing the composition.
[0056] The starting (b) ethylene-based polymer is heated to a temperature above the melting temperature of the (b) ethylene-based polymer, for example, 10° C. to 90° C., alternatively 10° C. to 40° C. above the melting temperature of the (b) ethylene-based polymer, before, during, and / or after forming the composition. This ensures that the (b) ethylene-based polymer melts rather than simply softens. Alternatively, a lower temperature may be utilized in combination with shear or mixing to ensure that the (b) ethylene-based polymer softens and / or melts.
[0057] The starting material (c) polydiorganosiloxane may be in liquid form or may be provided in the form of a solid carrier component. The solid carrier component is a combination that is solid at room temperature and includes (i) a polydiorganosiloxane as described above as starting material (c) and (ii) a polymer component selected from the group consisting of an ethylene-based polymer (as described above for starting material (b)), a maleated ethylene-based polymer (as described above for starting material (d)), or a combination of both an ethylene-based polymer and a maleated ethylene-based polymer. The solid carrier component may optionally further include a filler, as described below.
[0058] Alternatively, (a) the lignocellulosic filler and (c) the polydiorganosiloxane and at least one other starting material (e.g., one or more of the additional starting materials (e)-(n) above) may be combined to obtain a mixture, which may be combined with (b) the ethylene-based polymer (and any other additional starting materials) to obtain a composition. Combining (a) the lignocellulosic filler and (c) the polydiorganosiloxane may be considered to surface treat, wet, or pretreat (a) the lignocellulosic filler, which may further or alternatively surface treat (a) the lignocellulosic filler described herein. Alternatively, (a) the lignocellulosic filler and (c) the polydiorganosiloxane may be combined by spraying, impregnation, blending, or mixing. Combining the (a) lignocellulosic filler and the (c) polydiorganosiloxane may further include, for example, heating to combine the (c) polydiorganosiloxane with the (a) lignocellulosic filler. If pellets are used, the resulting combination of the (a) lignocellulosic filler and the (c) polydiorganosiloxane may be optionally compressed and then pelletized to form pellets. Combining the (a) lignocellulosic filler and the (c) polydiorganosiloxane may be performed in a separate process or may be incorporated into an existing (e.g., extrusion) process for making WPC articles in a premix step. In the premix step, the starting materials may be blended together before being fed to an extruder, for example, all or a portion of the (a) lignocellulosic filler, (c) polydiorganosiloxane, and (b) ethylene-based polymer, and one or more optional starting materials may be mixed in a premix step and then fed to an extruder.
[0059] Alternatively, the (c) polydiorganosiloxane may be present in a solid carrier component comprising, consisting essentially of, or consisting of the (a) lignocellulosic filler and the (c) polydiorganosiloxane, and the solid carrier component may be heated. Alternatively, the solid carrier component may be heated under vacuum. This heating may be performed for a number of reasons, including to evaporate the carrier vehicle (if any), to evaporate other components present in the mixture used to form the solid carrier component, or to improve the mechanical properties of the solid carrier component prior to use in the present method.
[0060] The composition may be formed, for example, under mixing or shear, in a suitable mixing device. For example, the composition may be formed in a vessel equipped with an agitator and / or mixing blades. The vessel may be an internal mixer, such as, for example, a Banbury type, a Sigma (Z) blade type, or a cavity moving type mixer. Alternatively, or in addition, the composition may be formed in or processed in an extruder, which may be any extruder, such as a single screw extruder with rotating and / or reciprocating (co-kneader) screws, as well as a multi-screw device with two or more screws, which may be arranged in a tangential or partially / fully intermeshing manner and rotate in either the same or counter-rotating direction. Alternatively, a conical extruder may be used to form the WPC compositions described herein.
[0061] In the above method for preparing a WPC article, the method further comprises forming a WPC article from the composition in step 2). The composition may be prepared, for example, in a container, then removed from the container and formed into an article in another device. Alternatively, the same device may be used to prepare the composition and subsequently form the WPC article. For example, the composition may be prepared and / or mixed in an extruder, and the extruder may be used to form the WPC article with the composition. Alternatively, the WPC article may be formed by molding, for example, using an injection molding, compression molding, or transfer molding process. The composition may be formed independently and then placed in a mold after forming.
[0062] The above method includes forming the WPC article from the composition, which may include forming the composition into a desired shape.The desired shape varies depending on the final use of the WPC article.Those skilled in the art will understand how to select and make the extrusion die and molding die based on the desired shape of the WPC article.
[0063] The process may be carried out continuously or semi-continuously in an extruder such as a twin screw extruder (with the screws rotating co-rotating partially or fully intermeshing, or counter-rotating in either a tangential or partially or fully intermeshing configuration). The starting material (c) polydiorganosiloxane (in a liquid state or as part of a solid carrier component) may be placed in the extruder simultaneously with (a) the lignocellulosic filler and (b) the ethylene-based polymer. Alternatively, the polydiorganosiloxane may be placed in the extruder after (b) the ethylene-based polymer is melted and before (a) the lignocellulosic filler is added. Alternatively, the polydiorganosiloxane may be placed in the extruder after (a) the lignocellulosic filler and (b) the ethylene-based polymer and before the WPC article exits the extruder. Alternatively, (a) the lignocellulosic filler may be placed in the extruder simultaneously with the polydiorganosiloxane and heated in the extruder to effect surface treatment of (a) the lignocellulosic filler with (c) the polydiorganosiloxane, and then (b) the ethylene-based polymer is placed in the extruder to obtain a mixture and the temperature is raised to a suitable temperature for compounding the mixture to form the WPC article. The extruder may have one or more zones, for example 1 to 3, or 3 to 8, or 1 to 12 zones, in which the starting materials may be added. The zones may be heated at different temperatures.
[0064] Alternatively, the (b) ethylene-based polymer may be placed in a first zone of the extruder and heated to within + / - 30°C of the melting temperature of the (b) ethylene-based polymer. The starting material (c) polydiorganosiloxane may be fed to a solid carrier component and placed in a second or subsequent zone of the extruder and heated to 10°C to 90°C above the melting temperature of the (b) ethylene-based polymer. As mentioned above, the temperature used is typically lower than the decomposition temperature of the starting material of the composition. Alternatively, the extruder die may also be heated, and the temperature utilized by the extruder (including any zone and die temperatures) may be selected such that the temperature does not exceed the decomposition temperature of the (a) lignocellulosic filler. The decomposition temperature of the (a) lignocellulosic filler will depend on the selection, as will be understood by those skilled in the art.
[0065] The above method can be used to make various WPC articles, such as building materials. Such WPC building materials include residential and / or commercial buildings and building products and applications, such as decking, railing, siding, fencing, window frames, trim, skirting, and flooring. When the building material is a decking, the method can optionally further include step 3), which is to add a capstock layer after step 2).
[0066] Solid Carrier Component Composition As mentioned above, (c) the polydiorganosiloxane may be added to the composition for preparing the WPC article in the form of a solid carrier component. The solid carrier component is: 5% to 20%, or 5% to less than 20%, of (i) the starting material (c) a polydiorganosiloxane as described above; (ii) More than 70% to 95% an ethylene-based polymer as described above for starting material (b); a maleated ethylene-based polymer as described above for starting material (d), and a polymer component selected from the group consisting of a combination of both an ethylene-based polymer and a maleated ethylene-based polymer; 0-10% of (iii) a filler; may comprise, consist essentially of, or consist of.
[0067] The polydiorganosiloxane in the starting material (i) solid carrier component is as described above for starting material (c). The starting material (ii) polymer component may include an ethylene-based polymer or may be free of a maleated ethylene-based polymer. The ethylene-based polymer in the solid carrier component is as described above for starting material (b). Alternatively, in the solid carrier component, the ethylene-based polymer may be selected from the group consisting of LLDPE, HDPE, and combinations thereof, or the ethylene-based polymer in the solid carrier component may be HDPE. Alternatively, the ethylene-based polymer in the solid carrier component may be HDPE having an I2 of greater than 2 g / 10 min, alternatively from 2.3 g / 10 min to 20 g / 10 min, alternatively from 2.3 g / 10 min to 12 g / 10 min, alternatively from 2.3 g / 10 min to 6 g / 10 min, alternatively from 4.4 g / 10 min to 20 g / 10 min, or alternatively from 6.8 g / 10 min to 20 g / 10 min. Alternatively, (ii) the polymer component may be a maleated ethylene-based polymer and the solid carrier component may be free of ethylene-based polymers. The maleated ethylene-based polymer for use in the solid carrier component may be as described above for starting material (d). Alternatively, (ii) the polymer component may comprise both an ethylene-based polymer and a maleated ethylene-based polymer. The filler in the solid carrier component is optional. If present, the filler may comprise a lignocellulosic filler as described above for starting material (a), an additional filler such as an inorganic filler as described above for starting material (e), or a combination of both a lignocellulosic filler and an additional filler. Alternatively, the filler in the solid carrier component may be a mineral filler, or the mineral filler may be selected from the group consisting of talc, calcium carbonate, and combinations thereof. Alternatively, the (e) additional filler may be talc. Alternatively, the solid carrier component may comprise from 5% to less than 20% of (i) the polydiorganosiloxane, from greater than 70% to 95% of (ii) the polymer component, and from 0 to 10% of (iii) the filler. Alternatively, the solid carrier component may comprise from 5% to 18% of (i) the polydiorganosiloxane, alternatively from 10% to 18%, alternatively from 10% to 15% of the polydiorganosiloxane.Alternatively, the solid carrier component may contain 0% filler. Alternatively, the solid carrier component may contain greater than 75% to 90% of the (ii) polymer component, or between 80% and 90% of the (ii) polymer component.
[0068] The solid carrier component is solid at ambient temperature and pressure (e.g., 25°C and 1 atm). The solid carrier component can be formed by combining the starting materials in any order. The solid carrier component can be prepared by forming a mixed composition from (ii) the polymer component and (i) the polydiorganosiloxane, and (iii) the filler, if present, by mixing or dispersing under shear using a suitable mixing device. For example, the mixed composition can be dispersed in a vessel equipped with an agitator and / or mixing blade. The vessel can be an internal mixer, such as, for example, a Banbury type, Sigma (Z) blade type, or a cavity moving type mixer. Alternatively or additionally, the mixed composition can be dispersed or processed in an extruder, which can be any extruder, such as a single screw extruder with rotating and / or reciprocating (co-kneader) screws, as well as a multi-screw device with two or more screws, which can be arranged in a tangential or partially / fully intermeshing manner and rotate in either the same or counter-direction. Alternatively, a conical extruder may be used to disperse the mixed compositions described herein.
[0069] The solid carrier component prepared as above can be reprocessed and prepared for feeding in a subsequent process. The mixed composition prepared as above can be, for example, a substantially continuous ribbon or discontinuous pellets or particles or powder. A substantially continuous ribbon can be formed by pressing the mixed composition through a die to form a continuous strand or tape, which is then cooled and then appropriately packaged. Alternatively, the strand or tape can be broken down to form pellets or powder. The mixing device can also generate the pressure and / or heat required to process the mixed composition through a die when the mixing device is an extruder, which can be any extruder, for example, a BUSS kneader, or a single screw extruder with rotating and / or reciprocating (co-kneader) screws, as well as a multi-screw device with two or more screws, which can be arranged in a tangential or partially / fully intermeshing manner and rotate in either the same or opposite directions. A conical extruder can be used to mix and pressurize the mixed composition. Alternatively, a gear pump can be used to generate the pressure required for extrusion after mixing the starting materials to form a mixture. The discontinuous form of the mixed composition can be created by chopping a continuous ribbon of the mixed composition into shorter lengths. Alternatively, a grinder or shredder may be used to reduce larger chunks of the mixed composition to a usable size.
[0070] The solid carrier component may be formed by a process carried out continuously or semi-continuously in an extruder such as a twin screw extruder (screws rotate simultaneously in partial or complete intermeshing, or counter-rotating in either tangential or partial or complete intermeshing configuration). Alternatively, (i) the polydiorganosiloxane may be placed in the extruder simultaneously with the polymer component and, optionally, (iii) the filler. Alternatively, (i) the polydiorganosiloxane may be placed in the extruder after (ii) the polymer component is melted (and before (iii) the filler is added to the mixed composition, if any). Alternatively, (i) the polydiorganosiloxane may be placed in the extruder after (iii) the filler, if any, and before (ii) the polymer component, and before the mixed composition exits the extruder. Alternatively, (iii) the filler may be placed in the extruder simultaneously with (i) the polydiorganosiloxane, and then the polymeric components may be placed in the extruder to obtain a mixture and the temperature may be raised to a temperature suitable for compounding the mixture. The extruder may have one or more zones, for example 1 to 3, alternatively 1 to 12, alternatively 3 to 12, alternatively 3 to 10 zones, in which the starting materials may be added. The zones may be heated at different temperatures and may incorporate various functional stages including conveying, melting, mixing, degassing, vacuum, pressurizing, and forming.
[0071] Alternatively, (ii) the polymeric component may be placed in a first zone of the extruder and heated to within + / - 30°C of the melting temperature of the polymeric component. (i) the polydiorganosiloxane may be placed in a second zone of the extruder and heated to 10°C to 90°C above the melting temperature of the (ii) polymeric component. The starting material (iii) the filler, if present, is placed in one or more of the first, second, or subsequent zones of the extruder. As noted above, the temperature used is typically below the decomposition temperature of the starting material of the solid carrier component. The mixture may be stripped to remove any air, moisture, or by-products prior to pressing and forming in the extruder die. The vacuum, pressing, and forming zones may be heated, and the temperature utilized in the extruder (including the temperature of any zones and die) does not exceed the decomposition temperature of the starting materials (i), (ii), and, if present, (iii). The decomposition temperatures of the starting materials (i), (ii), and (iii) will depend on the selection of these materials, as will be understood by those skilled in the art. The resulting extruded strands may be comminuted by any convenient means to form a solid support component.
[0072] The solid carrier component is typically in particulate form, and may be, for example, in the form of particles, pellets, or powder. The average particle size of the solid carrier component varies depending on the desired properties and its end use. The solid carrier component may be a powder. Alternatively, the solid carrier component may be a pellet. Pellets typically have a larger average particle size than powders. EXAMPLES
[0073] These examples are intended to illustrate the invention to one of ordinary skill in the art and should not be construed as limiting the scope of the invention as set forth in the claims. The starting materials in Table 3 were used in these examples. [Table 3]
[0074] In Table 3, the densities of the ethylene-based polymers and maleated ethylene-based polymers were measured according to ASTM D792-13, the I2 values were measured at 190°C and 2.16 Kg according to ASTM D1238-13, and the melt temperatures were measured by DSC according to ASTM D3418-15. The ethylene-based polymers and maleated ethylene-based polymers were commercially available from The Dow Chemical Company (Midland, Michigan, USA). The viscosities of the bis-vinyl terminated polydimethylsiloxanes were measured at 25°C and 0.1-50 RPM on a Brookfield DV-III cone and plate viscometer equipped with a #CP-52 spindle. The bis-vinyl terminated polydimethylsiloxanes were commercially available from Dow Silicones Corporation (Midland, Michigan, USA).
[0075] Reference Example 1 - Preparation procedure for WPC samples For all WPC samples, (a) the lignocellulosic filler was added independently of (b) the ethylene-based polymer, and (c) the polydiorganosiloxane through a secondary feed system located at a downstream location on the extruder barrel. By mixing solids into the fully molten ethylene-based polymer and polydiorganosiloxane blend, samples with higher filler content could be produced than if all materials were fed at the same location.
[0076] Test specimens were prepared using injection molding. Tensile bars were prepared and tested according to ASTM D638-14. Each composition was processed in the twin screw extruder and injection molding equipment under the same conditions for both formulations for consistency. In each example, the total feed rate, RPM, temperature, and equipment configuration remained constant for each composition for both the compounding extruder and the injection molding equipment.
[0077] The parameters associated with the extrusion process, as well as the average break strength, strand quality, and final injection molded tensile bar color of the wood plastic composite articles formed according to each example are set forth in the table below.
[0078] Melt temperatures were obtained using a thermocouple hand probe. This measurement was manual and required a certain level of skill, and therefore was subject to a high degree of variability. Experience has shown that results can vary by up to 10°C depending on the operator and technique. Care was taken to use the same operator and technique for these tests.
[0079] The extruder torque was recorded as a relative percentage of the maximum extruder torque.
[0080] The breaking strength was measured by preparing five samples and averaging them. The test was performed according to ASTM D638-14.
[0081] Color (Y) was also measured to quantify the level of thermal degradation occurring to the wood filler. Y value or brightness was measured as a measure of the darkening of the wood plastic composite during processing. Higher Y values correspond to lighter brown wood. Y values were measured using an average of two measurements on five separate injection molded tensile dogbone specimens (average of 10 measurements) using a BYK Spectroguide 45 / 0 glossmeter with a D65 illuminant and a 10° observer.
[0082] The comparative compositions are shown in Table 4. The amount of each starting material is in weight percent. [Table 4]
[0083] Table 5 shows the performance of the samples prepared as shown in Table 4. [Table 5]
[0084] The compositions of the examples are shown in Table 6. The amounts of each starting material are in weight percent. [Table 6]
[0085] The starting material (b) ethylene-based polymer was the balance of each sample as shown in Table 6. Table 7 shows the performance of the samples prepared as shown in Table 6. [Table 7]
[0086] In this Reference Example A, a 26 mm twin screw extruder was used to make the solid carrier component in pellet form. Starting material (b) ethylene-based polymer (PE), and optionally starting material (d) maleated ethylene-based polymer (MAPE), were fed into the first barrel section via the feed throat. Starting material (c) polydiorganosiloxane (Vi-terminated PDMS) was injected with mixing into the fourth of eleven barrel sections, above the screw section. The resulting composition was pelletized using a Gala underwater pelletizer to obtain consistency and collected for testing. The resulting samples 31-40 were cooled to room temperature and aged for a minimum of 48 hours before any testing.
[0087] In this Reference Example B, a 25 mm twin screw extruder was used to make the solid carrier component in pellet form. The starting material (b) ethylene-based polymer (PE), and optionally, the starting material (d) maleated ethylene-based polymer (MAPE), were fed into the first barrel section via a feed port. The starting material (c) polydiorganosiloxane (Vi-terminated PDMS) was injected with mixing into the fourth of the 12 barrel sections, onto the screw section. If used, (e) filler CaCO3 (untreated calcium carbonate having an average particle size of 3 μm) was also fed through the feed port of the first barrel section. The resulting composition was cooled by complete immersion in a water bath and pelletized using a strand pelletizer. The resulting Samples 41-46 were cooled to room temperature and aged for a minimum of 48 hours before any testing. In this Reference C, the exudation of polydiorganosiloxane from pellets prepared according to Reference A and Reference B was evaluated as follows: Each sample (4 g) was placed in a pre-weighed aluminum pan lined with Whatman™ #1 filter paper (5.5 cm diameter) such that the surface of the aluminum pan was completely covered with the filter paper but the filter paper did not bend. The pellets were spread evenly across the filter paper in a semi-uniform layer. The samples were left at room temperature on the bench or in a convection oven at said temperature for the specified time. After aging, the pellets were left at room temperature for at least 4 hours and the pellets were placed in a 20 mL scintillation vial. The filter paper was weighed to determine the aged filter paper weight. Exudation was determined according to the following formula:
number
[0088] The pellet composition (Table 8), aging conditions, and polydiorganosiloxane exudation (Table 9) are reported below. [Table 8] [Table 9]
[0089] The data in Tables 8 and 9 showed that solid carrier components could be prepared with the alkenyl-functional polydiorganosiloxanes described herein and HDPE 1. However, under the conditions tested in this example, pelletization with HDPE 2 and without MAPE was not possible; in this case, exudation was not measurable as indicated by NA, or "not applicable." Furthermore, solid carrier components could be made with low exudation (i.e., less than 5% exudation of the alkenyl-functional polydiorganosiloxane) using HDPE and maleated ethylene-based polymer (MAPE) when the alkenyl-functional polydiorganosiloxane was used in an amount less than 20%, or in an amount between 15% and 20%.
[0090] [Problem to be solved by the invention] WPC articles are generally made by high shear methods such as extrusion or injection molding. Lignocellulosic fillers are used to change mechanical properties, reduce cost (as they are typically less expensive than ethylene-based polymers), reduce density, and / or meet end-use requirements for various applications. Fillers generally increase the viscosity of molten ethylene-based polymers, so adding fillers can make the starting materials more difficult to process. If the starting materials are processed by high shear methods, these fillers may require more work for processing, and as a result, higher temperatures and limited extrusion rates may be required. This increase in temperature and stress can lead to thermal or mechanical degradation of the lignocellulosic fillers. Similarly, some ethylene-based polymers may suffer from degradation under mechanical or thermal stress from processing. This degradation leads to mechanical properties, discoloration, poor aesthetics, and / or other undesirable defects in the made WPC articles. Similarly, such processing difficulties lead to the need for additional high energy inputs for processing, increased torque, and reduced processing speeds. The combination of these effects can result in reduced mixer output and / or poor product quality. [Industrial Applicability]
[0091] The addition of polydiorganosiloxane during processing can substantially reduce torque. The reduction in torque also reduces energy requirements and reduces the melt temperature of the composition. Extrusion of the polydiorganosiloxane-containing compositions in Examples 1-24 resulted in 48%-69% torque compared to Comparative Examples 1-4, which did not contain a processing aid and had 84% torque. Additionally, Examples 1-3 and 5-24 have reduced melt temperatures (less than 245°C) compared to Comparative Examples 1-4. This reduction in temperature can allow for higher throughput, improved material properties, higher filler loading, improved properties of WPC articles, and / or reduced costs associated with manufacturing WPC articles when polydiorganosiloxanes are used. This reduction in torque, pressure, work, and temperature can also minimize or eliminate processing-related degradation of the ethylene-based polymer and / or filler. Surprisingly, it was found that this reduction in melting temperature (approximately 5°C to 30°C, or 10°C to 20°C) can be obtained by using polydiorganosiloxanes having alkenyl functional groups (e.g., bis-vinyl terminated polydimethylsiloxanes). Examples 1-3, 5-12, 14, 15, 17, 18, and 20-24 all exhibited temperatures below 240°C, compared to 245°C to 256°C for Comparative Examples 1-4. The reduction in darkening of the WPC articles was a measure of the reduction in degradation of the ethylene-based polymer and / or filler. Comparative Examples 1-4 all exhibited lower emission values (Y=4.3 to 6.9) compared to values of 7.9 to 16.3 for Examples 1-24. This indicates that the WPC articles prepared in the comparative examples were all darker than the WPC articles prepared by the examples, suggesting that the comparative examples showed more signs of degradation than the examples.
[0092] It has also been found that a polydiorganosiloxane having a viscosity of 2,000 mPa·s to 60,000 mPa·s can provide one or more of the above advantages to a composition for preparing a WPC article as compared to a control composition that does not contain a polydiorganosiloxane. Alternatively, the viscosity of the polydiorganosiloxane can be from 2,000 mPa·s to 10,000 mPa·s or from 2,000 mPa·s to 5,000 mPa·s.
[0093] Definitions and usage of terms All amounts, ratios, and percentages are by weight unless otherwise indicated. The Summary and Abstract of the Invention are incorporated herein by reference. The terms "comprising" or "comprise" are used herein in their broadest sense to mean and encompass the terms "including," "include," "consist(ing) essentially of," and "consist(ing) of." The use of "for example," "eg," "such as," and "including" to list examples does not limit the examples listed. Thus, "for example" or "such as" means "for example, but not limited to" or "such as, but not limited to," and encompasses other similar or equivalent examples. Abbreviations used herein have the definitions in Table 10. [Table 10]
[0094] The present invention has been described in an illustrative manner, and it is to be understood that the terminology used is intended to be in the nature of words of description rather than for purposes of limitation. With respect to any Markush group on which a description of a specific feature or aspect is relied upon herein, different, unusual and / or unexpected results may result from each element of the respective Markush group, independent of all other elements of the Markush group. Each element of the Markush group may be relied upon individually and / or in combination to fully support a particular embodiment within the scope of the appended claims.
[0095] Moreover, any ranges and subranges relied upon in describing the present invention are understood to be independently and inclusively within the scope of the appended claims and to describe and contemplate the entire range encompassing all and / or any values therein, even if such values are not expressly set forth herein. Those skilled in the art will readily recognize that the recited ranges and subranges fully describe and enable various embodiments of the present invention, and that such ranges and subranges may be further delineated into relevant halves, thirds, fourths, fifths, etc. By way of example only, the range "1-18" may be further detailed as the lower third, i.e., 1-6, the middle third, i.e., 7-12, and the upper third, i.e., 13-18, which are individually and collectively within the scope of the appended claims, and which may provide appropriate justification for certain embodiments within the scope of the appended claims, individually and / or collectively, upon which such embodiments may be relied upon. Furthermore, with respect to words defining or modifying a range, such as "at least," "greater than," "less than," "less than," etc., such words should be understood to include subranges and / or upper or lower limits.
[0096] EMBODIMENTS OF THE PRESENT DISCLOSURE In a first embodiment, a composition for preparing a wood-plastic composite article comprises: 40% by weight to 69% by weight of (a) a lignocellulosic filler; 30% by weight to 59% by weight of (b) an ethylene-based polymer; 1% by weight to 4% by weight of formula (c) [ka] wherein each R is an independently selected alkyl group of 1 to 18 carbon atoms, each R' is an independently selected alkenyl group of 2 to 18 carbon atoms, and the subscript x has a value sufficient to impart to the bis-alkenyl terminated polydialkylsiloxane a viscosity of 2,000 mPa·s to 60,000 mPa·s when measured at 25° C. and 0.1 to 50 RPM on a Brookfield DV-III cone and plate viscometer equipped with a #CP-52 spindle; 0 to 4 weight percent of (d) a maleated ethylene-based polymer; Including, Each is based on the combined weight of starting materials (a), (b), (c), and (d) in the composition.
[0097] In a second embodiment, in the composition of the first embodiment, the starting material (a) lignocellulosic filler comprises lignocellulosic material derived from wood, plants, agricultural by-products, cereal husks, sisal, bagasse, wheat straw, kapok, ramie, heneques, corn fiber or coir, nut shells, flax, jute, hemp, kenaf, rice husks, abaca, peanut husks, bamboo, straw, lignin, starch, or cellulose and cellulose containing products, and combinations thereof, and the starting material (a) is present in an amount of 45% to 65% by weight.
[0098] In a third embodiment, in the composition of the first or second embodiment, the lignocellulosic filler is a wood filler comprising lignin in an amount of 18% to 35% by weight, carbohydrates in an amount of 65% to 75% by weight, and optionally inorganic minerals in an amount of up to 10% by weight.
[0099] In a fourth embodiment, in the composition according to any one of the previous embodiments, the lignocellulosic filler comprises 29% to 57% by weight of α-cellulose.
[0100] In a fifth embodiment, the composition of any one of the preceding embodiments, wherein starting material (b) comprises an ethylene-based polymer selected from the group consisting of high density polyethylene (HDPE), medium density polyethylene (MDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), low density low molecular weight polyethylene (LDLMWPE), and combinations thereof, and starting material (b) is present in an amount of 35% to 50% by weight.
[0101] In a sixth embodiment, the composition of any one of the preceding embodiments, the ethylene-based polymer is selected from the group consisting of HDPE, LLDPE, and combinations thereof, and the ethylene-based polymer is present in an amount from 40% to 45% by weight.
[0102] In a seventh embodiment, the composition of any one of the previous embodiments, wherein the ethylene-based polymer comprises at least 50% recycled polyethylene.
[0103] In an eighth embodiment, in the composition of any one of the preceding embodiments, in starting material (c), each R is an alkyl group of 1 to 12 carbon atoms and each R' is an alkenyl group of 2 to 12 carbon atoms; subscript x has a value sufficient to impart a viscosity of from 2,000 mPa·s to 10,000 mPa·s to the polydiorganosiloxane; and starting material (c) is present in an amount of from 1 wt% to 2 wt%.
[0104] In a ninth embodiment, the composition of any one of the preceding embodiments, in starting material (c), each R is an alkyl group of 1 to 6 carbon atoms, each R' is selected from the group consisting of vinyl, allyl, and hexenyl, and subscript x has a value sufficient to impart a viscosity of from 2,000 mPa s to 5,000 mPa s to the polydiorganosiloxane.
[0105] In a tenth embodiment, in the composition of any one of the previous embodiments, the starting material (c) is a bis-vinyldimethylsiloxy-terminated polydimethylsiloxane.
[0106] In an eleventh embodiment, the composition of any one of the preceding embodiments, wherein starting material (d) is present, starting material (d) has a melt index measured according to ASTM D1238-15 at 190° C. / 2.16 Kg of 2 g / 10 min to 25 g / 10 min, and a maleic anhydride content of 0.25 wt.% to 2.5 wt.%.
[0107] In a twelfth embodiment, the composition of any one of the preceding embodiments, wherein the composition further comprises an additional starting material selected from the group consisting of: (e) an additional filler different from the lignocellulosic filler of the starting material (a); (f) a colorant; (g) a foaming agent; (h) a UV stabilizer; (i) an antioxidant; (j) a processing aid; (k) a preservative; (l) a biocide; (m) a flame retardant; (n) an impact modifier; and (o) a combination of two or more thereof.
[0108] In a thirteenth embodiment, in the composition described in any one of the previous embodiments, the starting material (e) is present in an amount of 10% by weight to 15% by weight, and the starting material (e) is a mineral filler.
[0109] In a fourteenth embodiment, a method for preparing a wood-plastic composite article comprises: (1) preparing a composition according to any one of the preceding claims by combining starting materials; (2) forming a wood-plastic composite article from the composition.
[0110] In a fifteenth embodiment, the method of the fourteenth embodiment further comprises the steps of: (i) mixing (a) the lignocellulosic filler and (b) the ethylene-based polymer and then adding (c) the bis-alkenyl terminated polydialkylsiloxane; (ii) heating (b) the ethylene-based polymer prior to and / or during formation of the composition to melt (b) the ethylene-based polymer; (iii) mixing the mixture of (a) the lignocellulosic filler and (c) the bis-alkenyl terminated polydialkylsiloxane and then adding (b) the polymer or (iv) any combination of (ii) and (i) or (iii); Further includes.
[0111] In a sixteenth embodiment, the method of the fourteenth embodiment further comprises: (i) (c) the bis-alkenyl terminated polydiorganosiloxane is liquid when the (c) bis-alkenyl terminated polydiorganosiloxane is combined with another starting ingredient of the composition; or (ii) (c) the bis-alkenyl terminated polydiorganosiloxane is present in a solid carrier component, the method further comprising melting the solid carrier component when the (c) bis-alkenyl terminated polydiorganosiloxane is combined with another starting ingredient of the composition.
[0112] In a seventeenth embodiment, the method of any one of the fourteenth to sixteenth embodiments further comprises: (i) forming the wood-plastic composite article from the composition further comprises forming the composition into a desired shape; (ii) forming the wood-plastic composite article from the composition comprises extruding the composition; (iii) forming the wood-plastic composite article from the composition comprises molding the composition; or (iv) any combination of (i)-(iii).
[0113] In an eighteenth embodiment, the method of any one of the fourteenth to seventeenth embodiments further includes that the wood-plastic composite article is useful as a building material selected from the group consisting of decking, railing, fencing, siding, trim, skirting, and window framing.
[0114] In a nineteenth embodiment, the building material of the method of the eighteenth embodiment is a decking material, and the method further comprises the step of 3) adding a capstock layer to the decking material after step 2).
[0115] In a twentieth embodiment, the solid carrier component is 5% by weight to less than 20% by weight of formula (i) [ka] wherein each R is an independently selected alkyl group of 1 to 18 carbon atoms, each R' is an independently selected alkenyl group of 2 to 18 carbon atoms, and the subscript x has a value sufficient to impart to the polydiorganosiloxane a viscosity of 2,000 mPa·s to 60,000 mPa·s when measured at 25° C. and 0.1 to 50 RPM on a Brookfield DV-III cone and plate viscometer equipped with a #CP-52 spindle; More than 70% by weight to 95% by weight of (ii) an ethylene-based polymer having a melt index greater than 2 g / 10 min, measured at 190° C. and 2.16 Kg according to ASTM D1238-13; Maleated ethylene-based polymers, and A combination of both (B) and (d); A polymer component selected from the group consisting of: 0-10% of (iii) a filler; Includes.
[0116] In a twenty-first embodiment, the bis-alkenyl terminated polydialkylsiloxane in the solid carrier component of the twentieth embodiment is one in which each R is an alkyl group of 1 to 12 carbon atoms and each R' is an alkenyl group of 2 to 12 carbon atoms, the subscript x has a value sufficient to impart a viscosity of from 2,000 mPa·s to 10,000 mPa·s to the polydiorganosiloxane, and the polydiorganosiloxane is present in an amount of from 10% to 20% by weight, based on the combined weight of all starting materials in the solid carrier component.
[0117] In a twenty-second embodiment, the polydiorganosiloxane in the solid carrier component of the twentieth or twenty-first embodiment is one in which each R is an alkyl group of 1 to 6 carbon atoms, each R' is independently selected from the group consisting of vinyl, allyl, and hexenyl, and the subscript x has a value sufficient to impart a viscosity of from 2,000 mPa·s to 5,000 mPa·s to the polydiorganosiloxane.
[0118] In a twenty-third embodiment, the polydiorganosiloxane in the solid carrier component according to any one of the twentieth to twenty-second embodiments is a bis-vinyl terminated polydimethylsiloxane.
[0119] In a twenty-fourth embodiment, the polymer component in the solid carrier component according to any one of the twentieth to twenty-third embodiments comprises an ethylene-based polymer.
[0120] In a twenty-fifth embodiment, the polymer component in the solid carrier component according to any one of the twentieth to twenty-fourth embodiments comprises high density polyethylene.
[0121] In a twenty-sixth embodiment, the polymer component in the solid carrier component in any one of the twentieth to twenty-fifth embodiments includes a high-density polyethylene having a melt index of 2.3 g / 10 min to 20 g / 10 min.
[0122] In a twenty-seventh embodiment, the polymer component in any one of the twentieth to twenty-sixth embodiments further comprises a maleated ethylene-based polymer.
[0123] In a twenty-eighth embodiment, the polymer component in any one of the twentieth to twenty-fifth embodiments does not include a maleated ethylene-based polymer.
[0124] In a twenty-ninth embodiment, the polymer component in any one of the twentieth to twenty-third embodiments includes a maleated ethylene-based polymer and does not include an ethylene-based polymer.
[0125] In a thirtieth embodiment, the filler is present in the solid carrier component of any one of the twentieth to twenty-ninth embodiments, and the filler comprises talc.
[0126] In a thirty-first embodiment, the solid carrier component in any one of the twentieth to twenty-ninth embodiments does not include a filler.
Claims
1. A composition for preparing a wood-plastic composite article, comprising: The composition comprises: 15% to 70% by weight of (a) a lignocellulosic filler; 29.5% to 84.5% by weight of (b) an ethylene-based polymer; 0.5% to 6% by weight of (c) a polydiorganosiloxane having the unit formula: (R 2 R’SiO 1/2 ) a (R 3 SiO 1/2 ) b (R 2 SiO 2/2 ) c (RR’SiO 2/2 ) d wherein each R is an independently selected monovalent hydrocarbon radical of 1 to 18 carbon atoms free of aliphatic unsaturation; each R' is an independently selected alkenyl radical of 2 to 18 carbon atoms; subscript a is from 0 to 2, subscript b is from 0 to 2, the sum (a+b)=2, subscript c is 0 or greater, subscript d is 0 or greater, the sum (a+d)≧1, and the sum (a+b+c+d) is sufficient to impart to said polydiorganosiloxane a viscosity of from 2,000 mPa·s to 60,000 mPa·s when measured at 25° C. and 0.1 to 50 RPM on a Brookfield DV-III cone and plate viscometer equipped with a #CP-52 spindle; and 1 wt. % to 3 wt. % of (d) a maleated ethylene-based polymer; Starting material (b) the ethylene-based polymer is selected from the group consisting of high density polyethylene (HDPE), medium density polyethylene (MDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), low density low molecular weight polyethylene (LDLMWPE), and combinations thereof; 1. A composition for preparing a wood-plastic composite article, each based on the total weight of starting materials (a), (b), (c), and (d) in said composition.
2. 2. The composition of claim 1, wherein the lignocellulosic filler comprises lignocellulosic material derived from wood, plants, agricultural by-products, grain husks, sisal, bagasse, wheat straw, kapok, ramie, heneques, corn fiber or coir, nut shells, flax, jute, hemp, kenaf, rice husks, abaca, peanut husks, bamboo, straw, lignin, or cellulose and cellulose-containing products, and combinations thereof, and wherein the starting material (a) is present in an amount of 45% to 65% by weight.
3. The polydiorganosiloxane has the formula 【Chemistry 1】 wherein each R is an independently selected monovalent hydrocarbon radical of 1 to 18 carbon atoms free of aliphatic unsaturation, each R' is an independently selected alkenyl radical of 2 to 18 carbon atoms, and subscript x has a value sufficient to impart to said polydiorganosiloxane a viscosity of from 2,000 mPa·s to 60,000 mPa·s when measured at 25° C. and 0.1 to 50 RPM on a Brookfield DV-III cone and plate viscometer equipped with a #CP-52 spindle.
2. The composition of claim 1, wherein the bis-alkenyl terminated polydiorganosiloxane is
4. 4. The composition of claim 3, wherein each R is an alkyl group of 1 to 12 carbon atoms and each R' is an alkenyl group of 2 to 12 carbon atoms, subscript x has a value sufficient to impart a viscosity of from 2,000 mPa·s to 10,000 mPa·s to said polydiorganosiloxane, and said polydiorganosiloxane is present in an amount of from 1.5% to 2% by weight.
5. 5. The composition of claim 4, wherein each R is a methyl group, each R' is a vinyl group, and subscript x has a value sufficient to impart a viscosity of from 2,000 mPa·s to 5,000 mPa·s to said polydiorganosiloxane.
6. 2. The composition of claim 1, wherein the maleated ethylene-based polymer is present and has a melt index, measured according to ASTM D1238-13 at 190° C. and 2.16 Kg, of 0.1 g / 10 min to 25 g / 10 min and a maleic anhydride content of 0.25 wt % to 2.5 wt %.
7. 13. The composition of claim 1, further comprising an additional starting material selected from the group consisting of: (e) an additional filler different from the lignocellulosic filler of starting material (a); (f) a colorant; (g) a foaming agent; (h) a UV stabilizer; (i) an antioxidant; (j) a processing aid; (k) a preservative; (l) a biocide; (m) a flame retardant; (n) an impact modifier; and (o) a combination of two or more thereof.
8. At least 5% but not more than 20% by weight of (i) polydiorganosiloxanes having the unit formula: (R 2 R’SiO 1/2 ) a (R 3 SiO 1/2 ) b (R 2 SiO 2/2 ) c (RR’SiO 2/2 ) d wherein each R is an independently selected monovalent hydrocarbon radical of 1 to 18 carbon atoms free of aliphatic unsaturation; each R' is an independently selected alkenyl radical of 2 to 18 carbon atoms; subscript a is from 0 to 2, subscript b is from 0 to 2, the sum (a+b)=2, subscript c is 0 or greater, subscript d is 0 or greater, the sum (a+d)≧1, and the sum (a+b+c+d) is sufficient to impart to said polydiorganosiloxane a viscosity of from 2,000 mPa·s to 60,000 mPa·s when measured at 25° C. and 0.1 to 50 RPM on a Brookfield DV-III cone and plate viscometer equipped with a #CP-52 spindle; greater than 70 weight percent and not greater than 95 weight percent of (ii) a polymer component that is a combination of an ethylene-based polymer and a maleated ethylene-based polymer selected from the group consisting of high density polyethylene (HDPE), medium density polyethylene (MDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), low density low molecular weight polyethylene (LDLMWPE), and combinations thereof; 0-10% filler; A solid carrier component comprising:
9. From 5% to 20% by weight of (i) a polydiorganosiloxane having the unit formula: (R 2 R’SiO 1/2 ) a (R 3 SiO 1/2 ) b (R 2 SiO 2/2 ) c (RR’SiO 2/2 ) d wherein each R is an independently selected monovalent hydrocarbon radical of 1 to 18 carbon atoms free of aliphatic unsaturation; each R' is an independently selected alkenyl radical of 2 to 18 carbon atoms; subscript a is from 0 to 2, subscript b is from 0 to 2, the sum (a+b)=2, subscript c is 0 or greater, subscript d is 0 or greater, the sum (a+d)≧1, and the sum (a+b+c+d) is sufficient to impart to said polydiorganosiloxane a viscosity of from 2,000 mPa·s to 60,000 mPa·s when measured at 25° C. and 0.1 to 50 RPM on a Brookfield DV-III cone and plate viscometer equipped with a #CP-52 spindle; greater than 70 weight percent and not greater than 95 weight percent of (ii) a polymer component that is a combination of an ethylene-based polymer and a maleated ethylene-based polymer selected from the group consisting of high density polyethylene (HDPE), medium density polyethylene (MDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), low density low molecular weight polyethylene (LDLMWPE), and combinations thereof; 0-10% filler; A solid carrier component comprising:
Citation Information
Patent Citations
For amine - silicone flame retardant plastics
JP1984500099A
Composite resin sheet
JP1986016965A
Organosilicone resin composition as lubricant for extrusion
JP1995088924A
Resin composition for polymer insulator containing kneaded mixture of ethylene resin and organopolysiloxane
JP1995179681A
Silicone-modified low-density polyethylene and its production
JP1998120836A